Indonesia's Foreign Policy in Organizing G20 Presidency in 2022 - Miranti, Feby Diah; Akim; Lanti, Irman G. (Yayasan Ilomata, 2025)
In 2022, Indonesia will have the opportunity for the G-20 Presidency under the leadership of President Joko Widodo. Judging from Indonesia's potential and the prospects of the G-20, this study will look at what kind of foreign policy Indonesia implements in organizing the G-20. Researchers use Rosenau's adaptive theory that foreign policy occurs due to changes in external, internal, and leadership of leaders in a particular country. The study uses qualitative methods with secondary sources from books, journals, official websites, and official documents. The research results from this article show that Indonesia's foreign policy in the G-20 Presidency is preservative Adaptation, meaning that the policy has been determined by external and internal changes and the leadership of the President at that time. External factors include the effects of COVID-19, climate change, and the Russia-Ukraine war. The internal factors are structural reform, digital transformation, and employment law policies. Finally, President Joko Widodo's leadership focuses on developing and improving the Indonesian economy.